Climate Change and Human Security in Zimbabwe - Mutizwa, Bismark (Journal of Humanities and Social Sciences (JHASS), 2023)
Across the global spectrum, climate change has proven to be problematic with no definitive way of solving it. At the same time, its effects on humanity have been catastrophic and detrimental, undermining all facets of human security such as food security, personal security, health security, environmental security, economic security, political security and community security. Zimbabwe has not been spared, as the scale and magnitude of climate change have proven to be more vicious and malignant owing it to a myriad of quagmires which among others include but are not limited to weak preparedness and emergence management systems, insufficient budget, lack of political will and poor community education campaigns. Using mixed method, the research examines the effects of climate change and human security in Zimbabwe with the primary purpose of coming up with organic and actionable policy alternatives that can be used to enhance human security. The paper concludes that, climate change undermines human security and there is need for urgent intervention from the government to invest in climate adaptation and mitigatory measures.